La comunicación en la escuela infantil: algunas consideraciones teóricas de utilidad para maestros e - Valenzuela Miranda, Julia (Didáctica. Lengua y Literatura, 2004)
This article aims to engage teacher trainees in a systematic reflection that supports and enriches the everyday work of the Infant Education teacher. The complex nature of the communication processes in the infant classroom is analysed. With this purpose, the autor examines on one hand the participants and other intervening elements in these communication processes and on the other hand the refined and complex relationships that are set up between them.